She-wolf : a cultural history of female werewolves - Priest, Hannah (Manchester Gothic (Manchester, England), 2016)
'She-Wolf' explores the cultural history of the female werewolf, from her first appearance in medieval literature to recent incarnations in film, television and popular literature.